(untitled) (Journal of the College of Basic Education, 2025)
The theory (TRIZ theory) emphasized a set of competencies of the individual in solving all problems in a creative way. Therefore, the aim of the research was: to identify the effect of an educational program based on TRIZ theory in developing selective attention and aesthetic taste in the subject of art history. This is done by constructing a measure of selective attention. In both its verbal and formal parts, building a scale for aesthetic taste, and its verbal and formal parts, and building the achievement test for the subject of the history of modern art, in addition to designing an educational program in the subject of the history of modern art. The researcher derived the research objective